Estimation of Genetic Linkage: An Outline - Murphyand, E. A.; Sherwin, R. W. (Methods of Information in Medicine, 1966)
Genes carried on the same chromosome pair are said to be »linked«. For the most part this interferes with their independent assortment. The probability that two genes on the same chromosome part company during hereditary transmission is the recombination value (χ); in man it ranges from zero (corresponding to pleiotropy) to 0.5 (independent assortment). From data, χ niay be estimated by the method of maximum likelihood which though simple in principle may involve tedious calculations when applied to human pedigrees. A computer program has been devised to carry out the otherwise intractable calculations required to make efficient estimates from large human pedigrees. The principles of linkage estimation in man are presented as an introduction to the classic texts on the subject. Factors important in the estimation of linkage are discussed. More recent Bayesian elaborations of these methods are outlined.